LITERATURE, IDENTITY, IMPERIALISM: FABULOUS MONSTERS IN THE CLASSROOM - Hunter, Nigel (fólio - Revista de Letras, 2018)
This text presents some reflections on certain aspects of literature teaching at the present time, contesting the reductive orthodoxies of politically-charged reading procedures and the leading assumptions of identity politics. By reference to a number of literary works of culturally diverse origins, accompanied by a commentary on their complex engagement with a range of related questions, an attempt is made to claim for literature a more ample field, of greater psychological and social resonance, than such analyses as those favoured by the ‘cultural studies’ movement generally allow. The text was written originally to be delivered as a talk leading to debate, and remains inscribed with many of the markers of oral discourse.